Spontaneous pneumoperitoneum secondary to intestinal pneumatosis: an uncommon cause of acute abdomen - Vives, Jonathan Salgado; Serna, Enrique Chávez; Bustos, Fernando Uraik Hernandez; Herrera, Guadalupe Grisel Yañez (International Journal of Research in Medical Sciences, 2021)
Intestinal pneumatosis is a rare entity characterized by gas accumulation in the submucosa and or subserosa of the intestinal tract wall and is generally associated with other diseases, the primary presentation is rare. Most of the cases are asymptomatic, being infrequent the presentation as an acute abdomen secondary to a spontaneous pneumoperitoneum. We report the case of a patient with systemic sclerosis, who presented to the emergency department with abdominal pain and intestinal obstruction, without improvement to conservative treatment and with progression to acute abdomen, for which surgical treatment was performed showing intestinal pneumatosis that compromised the entire small intestine.